“Fruit basket upset”: Spatially explicit crop mixture responses to climatic and economic pressures - Robertson, Richard D.; Petsakos, Athanasios; Cenacchi, Nicola; Gotor, Elisabetta (Emerald Publishing Limited, 2024)
Purpose The choice of crops to produce at a location depends to a large degree on the climate. As the climate changes and food demand evolves, farmers may need to produce a different mix of crops. This study assesses how much cropland may be subject to such upheavals at the global scale, and then focuses on China as a case study to examine how spatial heterogeneity informs different contexts for adaptation within a country.